2011
DOI: 10.1111/j.1365-3180.2011.00896.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of environmental factors on seed germination and seedling emergence of invasive Ceratocarpus arenarius

Abstract: Ceratocarpus arenarius is a problematic and noxious weed of dryland farming in North Khorasan, Iran. Experiments were conducted to investigate the mechanism of seed dormancy, as well as the effect of environmental factors on germination and emergence of this species. Results showed that the pericarp is the major obstacle to seed germination; seeds without an intact pericarp had germination rates exceeding 90%. Ceratocarpus arenarius had identical germination rates in either light ⁄ dark and continuous dark con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
58
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(66 citation statements)
references
References 25 publications
8
58
0
Order By: Relevance
“…The interactive effect of water potential on germination rate and percentage of safflower has also been reported in other species (Kebreab and Murdoch, 1999;Ebrahimi and Eslami 2012;Nandula et al, 2006;Bolfrey-Arku et al, 2011).…”
Section: Resultssupporting
confidence: 66%
“…The interactive effect of water potential on germination rate and percentage of safflower has also been reported in other species (Kebreab and Murdoch, 1999;Ebrahimi and Eslami 2012;Nandula et al, 2006;Bolfrey-Arku et al, 2011).…”
Section: Resultssupporting
confidence: 66%
“…A study recently has been published on seed germination of C. arenarius growing as an arable weed in dryland crops (wheat, barley and lentils) in northern Iran (Ebrahimi and Eslami, 2012). The authors made a mass collection of seeds (dispersal units), presumably a mixture of our units b -f (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…1). They (Ebrahimi and Eslami, 2012) subsequently removed the pericarp ( probably bracteoles) from the fruits [ probably fruits (utricles) with enclosing bracteoles] and used the seeds ( probably utricles without bracteoles) in the majority of their germination tests. They erroneously concluded that their fruits have physical dormancy, which is not known to occur in Amaranthaceae (including Chenopodiaceae) (Baskin et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations